Ummatan Wasatan Menurut Hamka dan Thabari (Studi Komparasi Tafsir Al-Azhar dan Tafsir Al-Thabari Terhadap Surat Al-Baqarah Ayat 143 - Supriyanto, Fredy Susilo (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
Allah made Muslims as ummatan wasatan as mentioned in Al-Baqarah verse 143, ummatan wasatan means a people whose position is in the middle, meaning balanced in doing something so that it is not excessive to the interests of the world and does not shackle itself from worldly things. So being ummatan wasatan, his life can be balanced between his relationship with Allah the creator and with His creation, so that even if there is a slight difference in something, it does not affect the harmony between them because in fact ummatan wasatan means an ideal society whose life is sustainable. This study aims to determine the meaning of ummatan wasatan as well as the similarities and differences in the interpretation of ummatan wasatan in Al-Quran letter Al-Baqarah verse 143 based on Tafsir Al-Azhar and At-Thabari. This type of research is library research, which is research conducted using literature. And the method the author uses is descriptive analysis, which is observing a symptom or event which then the results of the research will be processed and analyzed to draw conclusions using the muqarin method (comparison). Hamka and Thabari both interpret ummatan wasatan as a people whose position is in the middle or balanced and does not lean to one side unlike the Jews who only lean towards the world and the Christians who lean towards the hereafter. And that Muslims are the chosen and just people who will later become witnesses to the previous Prophets. And there are differences in the interpretation of the two that Hamka mentions from the event of moving the Qibla to make the formation of ummatan wasatan or a new ummah because it is proven who survives the Prophet and the one who shows a challenge to him. And the difference in interpretation in interpreting the verse looks different because Hamka tends to use interpretation bir-ra,yi while Thabari uses interpretation bil ma'tsur so that in interpreting ummatan wasatan is a fair people in his interpretation Thabari mentions many related traditions.